Commemorative literacies and labors of justice resistance, reconciliation, and recovery in Buenos Aires and beyond - Damico, James S.; Lybarger, Loren D. 1964-; Brudney, Edward (Routledge, Taylor & Francis Group, 2022)
"This book examines literacy practices of commemoration marking the 40th anniversary of the March 24, 1976 coup in Argentina. Drawing on research conducted across three distinct sites in Buenos Aires in March 2016 -- a public university, a Catholic church, and a former naval base and clandestine detention center transformed into a museum space for memory and justice -- this book sheds light on the ways commemorative literacies at these locations work spatially to mobilize memory of the past to address and advance justice concerns in the present. These labors of justice manifest in three ways: as resistance, reconciliation, and recovery. Damico, Lybarger, and Brudney also demonstrate how these particular kinds of commemorative literacies resonate transnationally in ways that necessitate a commitment to commemorative ethics. This book is ideal not only for researchers, graduate students, and scholars in literacy studies, but also for all those working in related fields, including memory studies, religious studies, area studies, and Latin American studies, to address issues pertaining to memory, testimony, transitional justice, state repression, and human rights in Argentina, Latin America, or the Global South, more generally"--